Curiosity (a desire to know): born or learned ? - Bùi Tuyên (Journal of Technical Education Science, 2012)
Subjectivity is the only way we experience the world. Newborns have no solid ideas in mind but the desire to explore the environment for survival is already encoded in genes. Gradually the world is presented as a fleeting bundle of perception and images in our mind. Our mind will always struggle to connect and explain events, to find out how and why. Why does our thirst for knowledge seem unquenchable? Is desire to learn inherent in certain animals only? These questions have been around for a long time and the final answer may not exist. This paper is an attempt to bring in a new look, it argues that desire to know the surroundings is universal.